Vitamin D analogue: potent antiproliferative effects on cancer cell lines and lack of hypercalcemic activity. - Ferronato, María Julia (2015)
The active form of vitamin D3, 1α,25(OH)2D3, plays a major role in maintaining calcium/phosphate homeostasis. In addition, it is a potent antiproliferative and pro-differentiating agent. Unfortunately, it usually causes hypercalcemia in vivo when effective antitumor doses are used. It has therefore been found necessary to synthesize new analogues that retain or even increase the antitumor effects but preclude hypercalcemia. This report presents the synthesis of a novel Gemini vitamin D analogue (UVB1) and its biological evaluation. We demonstrate that this compound has potent antitumoral effects over a wide panel of tumor cell lines while showing lack of hypercalcemic activity and toxicity effects in in vivo assays.